Discourse communities on archival education and research: a domain analysis of the Archival Education and Research Initiative - AERI (2008-2021) - Alencar, Maira Fernandes [UNESP]; Tognoli, Natalia Bolfarini; Cervantes, Brigida Maria Nogueira (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2024)
In the international context, the discourse community Archival Education Research Initiative, made up of faculty members and students in the field of archives, works with a focus on the educational and research dimension, guiding the debate on historically marginalized communities and how they are (under)represented in archives. Considering that this debate has also been taking place in the Brazilian context in recent years, this paper aims to characterize this discursive community based on its actors and their scientific productions. The methodology employed is exploratory and descriptive. Domain Analysis was used through two lenses: (a) epistemic, focusing on the biography of the community members, and (b) scientific production, focusing on the publications of its members in the period 2008-2021. The results were systematized along two axes: the epistemic profile, which is a biographical aspect, and the scientific structure profile. The members' biographies cover two dimensions: research dealing with community archives, human rights, critical theory, social justice, and post-colonialism, and research dealing with archival dimensions concerning information and communication technologies and knowledge organization.
Keywords: Archival Education Research Initiative; archival science; critical archival studies; domain analysis; discourse community